The Influence of Employability and Soft Skills Training on Job Satisfaction among Generation Z Employees at PT Telkom Akses - Pira Azara; Hendra Harmain; Atika Atika (Fakultas Syariah IAIN Langsa, 2026)
The ideal condition in modern organizations requires Generation Z employees to possess a high level of employability as well as adequate soft skills to support job satisfaction and organizational effectiveness. However, the actual conditions in the workplace indicate that some Generation Z employees have not fully met these demands, particularly in aspects of communication, teamwork, and adaptation to technology-based work environment changes. Based on these conditions, this study aims to examine and analyze the influence of employability and soft skills training on the job satisfaction of Generation Z employees at PT Telkom Akses, Simpang Limun Branch Office. This study uses a quantitative approach with an explanatory design. The sample consists of 96 Generation Z employees selected using purposive sampling technique with the Lemeshow formula. Data were collected through a Likert-scale questionnaire using a cross-sectional approach and analyzed using multiple linear regression with the assistance of SPSS. The results show that employability has a positive and significant influence on the job satisfaction of Generation Z employees. Soft skills training also has a positive and significant influence on job satisfaction, with a more dominant contribution compared to employability. Simultaneously, both variables have a significant influence on job satisfaction. The coefficient of determination indicates that employability and soft skills training are able to explain a considerable proportion of the variation in Generation Z employees’ job satisfaction. These findings emphasize the importance of strengthening both technical competencies and soft skills in human resource development strategies within organizations.